Infinite Paths of Minimal Length on Suborbital Graphs for Some Fuchsian Groups - Khuanchanok Chaichana; Pradthana Jaipong (International Journal of Mathematics and Mathematical Sciences)
In this study, we work on the Fuchsian group Hm where m is a prime number acting on mℚ^ transitively. We give necessary and sufficient conditions for two vertices to be adjacent in suborbital graphs induced by these groups. Moreover, we investigate infinite paths of minimal length in graphs and give the recursive representation of continued fraction of such vertex.